Determinants of Intention to Adopt the Nigerian Digital Currency, the eNaira: A Conceptual Framework (Journal of Entrepreneurship and Business, 2025)
This research extends the Unified Theory of Adoption and Use of Technology (UTAUT) model by incorporating variables such as security, government regulatory, and a new moderating variable, technology awareness. This is achieved through an empirical review of relevant studies and the development of a conceptual framework for adopting  Nigeria's digital currency, the eNaira. The proposed framework aims to guide future research on technology adoption in developing countries. Existing studies reveal that digital currencies have higher adoption rates in Western nations compared to non-Western ones. However, the distinct challenges and characteristics of emerging nations limit the direct application of findings from developed countries. Therefore, considering Nigeria's specific context, this study examines the critical factors influencing the intention to adopt the eNaira. These factors are integrated into a framework designed to address issues related to the adoption of eNaira among Nigerians. This research enhances and validates the UTAUT model, contributing to the academic literature. Practically, it offers insights into key factors that can improve eNaira adoption, supporting government organizations and policymakers in increasing the digital currency's adoption in Nigeria and any other developing country.